Bistable polymer-dispersed cholesteric liquid crystal thin film enabled by a stepwise polymerization. Issue 73 (9th August 2015) - Wang, Huihui; Wang, Ling; Chen, Mei; Li, Tongda; Cao, Hui; Yang, Dengke; Yang, Zhou; Yang, Huai; Zhu, Siquan
<x xml:space="preserve">Abstract</x> By using a proper polymer network and an ion-doped cholesteric liquid crystal with negative dielectric anisotropy, bistable polymer-dispersed liquid crystal thin films were prepared by first photo-curing, and then thermally curing.